2010
DOI: 10.1038/ng.605
|View full text |Cite
|
Sign up to set email alerts
|

Systematic screens of a Candida albicans homozygous deletion library decouple morphogenetic switching and pathogenicity

Abstract: Candida albicans is the most common cause of serious fungal disease in humans. Creation of isogenic null mutants of this diploid organism, which requires sequential gene targeting, allows dissection of virulence mechanisms. Published analyses of such mutants show a near-perfect correlation between C. albicans pathogenicity and the ability to undergo a yeast-to-hypha morphological switch in vitro. However, most studies used mutants constructed with a marker that is itself a virulence determinant and therefore c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
674
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(697 citation statements)
references
References 51 publications
21
674
0
2
Order By: Relevance
“…For example, experiments with a doxycycline-inducible transcription factor (NRG1) that governs hyphae formation have shown that the ability to form hyphae is continually required for the lethality associated with systemic candidaisis (6). Likewise, many mutants defective in hyphae formation are nonpathogenic (7) and poor at biofilm formation, although this correlation is not absolute (38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, experiments with a doxycycline-inducible transcription factor (NRG1) that governs hyphae formation have shown that the ability to form hyphae is continually required for the lethality associated with systemic candidaisis (6). Likewise, many mutants defective in hyphae formation are nonpathogenic (7) and poor at biofilm formation, although this correlation is not absolute (38).…”
Section: Discussionmentioning
confidence: 99%
“…albicans morphogenetic conversions (the reversible switching between yeast and filamentous forms) are important for multiple aspects of C. albicans biology, pathogenicity and biofilm development. Morphogenesis is considered a key virulence trait of the fungus, since strains locked in a given morphology exhibit attenuated virulence (Noble et al, 2010;Saville et al, 2003). Hyphal growth and the coordinated expression of hypha-specific genes are also important for virulence, as they promote attachment to biotic and abiotic surfaces (Fu et al, 2002;Nobile et al, 2008), tissue invasion (Gow et al, 2002) and escape from phagocytic immune cells (Lorenz et al, 2004).…”
Section: Formation and Structure Of Candida Biofilmsmentioning
confidence: 99%
“…The success of C. albicans as a major fungal pathogen of humans relies on a number of pathogenic traits, among which its capacity to grow and switch between at least three distinctive morphological forms: budding yeast, pseudohyphae and hyphae [2][3][4][5]. The morphogenetic transition has been commonly described as a critical trait for survival and virulence in the host, even though the analysis of a wide array of C. albicans knock-out mutants suggests that pathogenesis can be dissociated to some extent from morphological switching [6][7][8].…”
Section: Introductionmentioning
confidence: 99%